Webizing interactive CAD review system using super multiview autostereoscopic displays - Seo, D.; Lee, Y.; Yoo, B. (Communications in Computer and Information Science, 2017)
A glasses-free super multi-view display has emerged alongside the development of optical technologies. However, the display is not yet widely used because its content remains in the early stages of only image or video without user interaction. Expanding the display market would require content that can take advantage of the display. In this paper, we propose a webized interactive CAD review system that uses super multi-view autostereoscopic displays with an application facilitating the popularization of super multi-view displays. The content for the display is described by web technologies such as HTML5, CSS, and JavaScript. The proposed system renders the content through a web browser and handles user interactions via JavaScript. A user can view autostereoscopic images with a sense of depth through motion parallax using the display and control the content remotely using gesture interaction devices. We present an example of content using a prototype implementation to verify our approach’s usefulness. ？ Springer International Publishing AG 2017.